The making of green knowledge: Environmental politics and cultural transformation - Jamison, Andrew (Cambridge University, 2013)
This book provides a comprehensive introduction to the politics of the environment and the development of environmental knowledge. Focusing on the quest for more sustainable forms of socio-economic development, it places environmental politics within a broad historical perspective, and examines the different political strategies and cultural practices that have emerged.